"Euroslam" - is it ridda or time consuming? - Hazyr-Ogly, T. (Ukrai͏̈ns'ke relihijeznavstvo, 2006)
Islam is now professed by the population of many countries in the Middle East, Asia, Africa, Europe. According to the World Islamic League, as of 2004, there were 1.2 billion Islamic followers in different countries (around 120 countries). In 35 countries, Muslims now make up 95-99 percent of the population, in 17 countries Islam is the state religion, and in 25 states, Muslims are an influential minority. Muslim communities are overwhelmed in Asia and North Africa. But they are also present in Europe, the US and Japan. According to statistics from the European Monitoring Center and Xenophobia (EUMC), Islam is the only religious religion in the world over the past 100 years, from 13 to 19.5 percent.